DEFENSE MECHANISM IN RAMBO: THE FIRST BLOOD FILM IN REFERENCE TO SEMIOTIC - Doni Sehat Sitanggang; Sri Minda Murni; Meisuri Meisuri (State University of Medan, 2018)
This study dealt with defense mechanisms in Rambo : The First Blood Film in reference to semiotic. It employed descriptive qualitative research method. This study was aimed to analyze: (1) The kinds of defense mechanisms experienced by Rambo and (2) why defense mechanism affected the utterance and action of Rambo in reference of semiotic. The data of this study were dialogues statement and figure that contained defense mechanisms. The theories were applied by the writer from Sigmund freud (1993) about defense mechanism and Chandler (2007) about semiotic. Based on the analysis, there were five kinds of defense mechanism used by Rambo, namely Denial (23,8%), Displacement (4,8%). Projection (42,9), Repression (14,3%), and Reaction Formation (14,3%) where Rambo used projection defense mechanisms the most. Fear that steam from trauma and to avoid conflict were the defense mechanism that happened and used by Rambo. Keywords: Defense mechanisms, semiotic, Rambo: The First Blood